PENGARUH FAKTOR – FAKTOR PEMELIHARAAN TERHADAP KENYAMANAN BANGUNAN GEDUNG SEKOLAH TINGGI TEKNOLOGI PAGAR ALAM - Abdi Nasrullah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Building maintenance aims to maintain the function of the building itself. Therefore, an assessment of the effect of building maintenance factors was carried out, to determine the condition of building maintenance, how much influence building maintenance on comfort and knowing the most dominant factor influencing the comfort of building users.. This research was conducted in the technology pagaralam college at Pagar Alam with a total of 56 respondents. Data was processed using simple liniear regression analysis ( with the F test ) and multiple liniear regression (partial t test). After being declared valid during the validity test, realiability test, the classic assumptions are the normality test, the multicollinearity test, the heteroscesdasticity test, and the autocorrelation test. From the f test obtained f count > f table, i.e. 294,947 > 2,01 and significant value 0,000 < 0,05, so H0 was rejected and Ha was accepted, this right mean that there was a significant influence of the vVariabels of building maintenance (X) on the convinience of working (Y) together. from the test it was found that each vVariabel X1 to X11 produced a value of t arithmetic > t table and significant value < 0,05, so H0 was rejected and Ha was accepted. So each building maintenance vVariabel (X) had an influence on work comfort (Y). Value of the coefficient of determination (R2) = 0,994 or 99,4%. The most dominant maintenance vVariabel in influencing building maintenance was ceiling maintenance vVariabel with beta value (β) = 0,186.